The role of mislocalized phototransduction in photoreceptor cell death of retinitis pigmentosa. - Takeshi Nakao; Motokazu Tsujikawa; Shoji Notomi; Yasuhiro Ikeda; Kohji Nishida (PLoS ONE)
Most of inherited retinal diseases such as retinitis pigmentosa (RP) cause photoreceptor cell death resulting in blindness. RP is a large family of diseases in which the photoreceptor cell death can be caused by a number of pathways. Among them, light exposure has been reported to induce photoreceptor cell death. However, the detailed mechanism by which photoreceptor cell death is caused by light exposure is unclear. In this study, we have shown that even a mild light exposure can induce ectopic phototransduction and result in the acceleration of rod photoreceptor cell death in some vertebrate models. In ovl, a zebrafish model of outer segment deficiency, photoreceptor cell death is associated with light exposure. The ovl larvae show ectopic accumulation of rhodopsin and knockdown of ectopic rhodopsin and transducin rescue rod photoreceptor cell death. However, knockdown of phosphodiesterase, the enzyme that mediates the next step of phototransduction, does not. So, ectopic phototransduction activated by light exposure, which leads to rod photoreceptor cell death, is through the action of transducin. Furthermore, we have demonstrated that forced activation of adenylyl cyclase in the inner segment leads to rod photoreceptor cell death. For further confirmation, we have also generated a transgenic fish which possesses a human rhodopsin mutation, Q344X. This fish and rd10 model mice show photoreceptor cell death caused by adenylyl cyclase. In short, our study indicates that in some RP, adenylyl cyclase is involved in photoreceptor cell death pathway; its inhibition is potentially a logical approach for a novel RP therapy.